Phosphorylation of MAD2 at Ser195 Promotes Spindle Checkpoint Defects and Sensitizes Cancer Cells to Radiotherapy in ATM Deficient Cells - Wang, Yang; Yu, Tianyu; Han, Yi; He, Yazhi; Song, Yiran; Guo, Leiming; An, Liwei; Yang, Chunying; Wang, Feng (Frontiers in Cell and Developmental Biology, 2022)
The spindle assembly checkpoint (SAC) is a critical monitoring device in mitosis for the maintenance of genomic stability. Specifically, the SAC complex comprises several factors, including Mad1, Mad2, and Bub1. Ataxia-telangiectasia mutated (ATM) kinase, the crucial regulator in DNA damage response (DDR), also plays a critical role in mitosis by regulating Mad1 dimerization and SAC. Here, we further demonstrated that ATM negatively regulates the phosphorylation of Mad2, another critical component of the SAC, which is also involved in DDR. Mechanistically, we found that phosphorylation of Mad2 is aberrantly increased in ATM-deficient cells. Point-mutation analysis further revealed that Serine 195 mainly mediated Mad2 phosphorylation upon ATM ablation. Functionally, the phosphorylation of Mad2 causes decreased DNA damage repair capacity and is related to the resistance to cancer cell radiotherapy. Altogether, this study unveils the key regulatory role of Mad2 phosphorylation in checkpoint defects and DNA damage repair in ATM-deficient cells.